BOKO HARAM: A THREAT TO NIGERIAN NATIONAL SECURITY - Ntamu, G. U.; Ekpenyong, Ekpenyong Obo (European Scientific Journal, ESJ, 2014)
We live in a world that violence now is the order of the day and prevalent in human relations. One of the greatest threats that the globe is facing today is terrorism. Our nation, Nigeria, is at the instant, confronted with intimidation from Boko Haram. The security of any nation is very important in that where peace, safety lives and properties are not guaranteed; there can be no meaningful development. This work showed that the insurgent is a threat to National Security in Nigeria. This work will also attempt to examine the state of affairs in Nigeria with regard to security by means of looking at carefully a number of the major factors so as to have helped to bring about the common growth in social dissatisfaction, with which the insurgent Boko Haram has been skilful to take advantage of.